Millennial Community Participation in Tourism Village Development: Evidence from Sumberbulu, Central Java - Kusherdyana; Syaeful Muslim; Misran Misran; Singgih Tri Wibowo (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2023)
Sumberbulu Hamlet is a Tourism Village located in Karanganyar Regency, Central Java Province. The people of this village are trying to develop their village into an advanced tourist village that is attractive for many tourists to visit. However, in its development, community participation in village development is felt to be not optimal, especially the participation of people who are classified as millennials. Therefore, this study aims to reveal the forms and levels of millennial community participation in efforts to develop their villages. This study used a descriptive qualitative method with informants from several residents belonging to the millennial age group and village officials. The results of the study show that the form of participation is included in Pseudo-Participation, while the level of participation, in general, is at the Partnership level. It is recommended that the village government and other stakeholders can improve education and training for millennial communities in the development of tourism villages, so that they can strengthen their abilities and knowledge in developing tourism in Sumberbulu village.